The Catalyst Effect : 12 Skills and Behaviors to Boost Your Impact and Elevate Team Performance - Toomer, Jerry (Emerald Publishing, 2018)
Provides a practical, research-based roadmap for developing and applying twelve key competencies to multiply an individual's impact, elevate the performance of others, and accelerate progress toward mission-oriented goals, generating greater value.